Implications of Managerial Financial Literacy on Generation Z's Consumptive Behavior - Idris, Moch; Priono, Hero (The Faculty of Education and Teaching Training, 2025)
This study aims to analyze the implications of managerial financial literacy on the consumptive behavior of Generation Z, while also considering the influence of hedonism and social media as supporting variables. The research focuses on users of the Shopee PayLater service in Surabaya who belong to the Generation Z age group (15–29 years). A quantitative approach was employed, with a total of 100 respondents determined using the Slovin formula and selected through a closed questionnaire distributed via Google Forms. Each variable was measured using a Likert scale and analyzed through multiple linear regression with the assistance of SPSS version 27. The findings indicate that managerial financial literacy, hedonism, and social media each have a significant influence on consumptive behavior. These results align with the Theory of Planned Behavior, which asserts that individual perceptions and social pressures play a crucial role in consumption decision-making. This study contributes theoretically to a better understanding of managerial financial literacy as a control mechanism over consumptive behavior and offers practical implications for the development of financial education strategies that are adaptive to the dynamics of digital consumption among young consumers.